Serum concentrations of tumour necrosis factor in dogs naturally infected with Babesia Canis and its relation to severity of disease - Jacobson, Linda S. (University of Pretoria, 2013)
Dissertation (MMed Vet (Med))--University of Pretoria, 2001.